Celebrating Rose Watkins' 64th Birthday-207 Geneva Avenue - Watkins, Howard::::::::: (1983)
Jean Richards, Rose Watkins, Sharon Bailey, Howard Watkins with beard, Stephanie Richards; Adam Watkins walking behind